Clinical and microbiological effect of a combination of hydroxychloroquine and azithromycin in 80 COVID-19 patients with at least a six-day follow up: A pilot observational study. Issue 34 (March 2020) - Gautret, Philippe; Lagier, Jean-Christophe; Parola, Philippe; Hoang, Van Thuan; Meddeb, Line; Sevestre, Jacques; Mailhe, Morgane; Doudier, Barbara; Aubry, Camille; Amrane, Sophie; Seng, Piseth; Hocquart, Marie; et al.
Abstract: Background: We need an effective treatment to cure COVID-19 patients and to decrease virus carriage duration. Methods: We conducted an uncontrolled, non-comparative, observational study in a cohort of 80 relatively mildly infected inpatients treated with a combination of hydroxychloroquine and azithromycin over a period of at least three days, with three main measurements: clinical outcome, contagiousness as assessed by PCR and culture, and length of stay in infectious disease unit (IDU). Results: All patients improved clinically except one 86 year-old patient who died, and one 74 year-old patient still in intensive care. A rapid fall of nasopharyngeal viral load was noted, with 83% negative at Day7, and 93% at Day8. Virus cultures from patient respiratory samples were negative in 97.5% of patients at Day5. Consequently patients were able to be rapidly discharged from IDU with a mean length of stay of five days. Conclusion: We believe there is urgency to evaluate the effectiveness of this potentially-life saving therapeutic strategy at a larger scale, both to treat and cure patients at an early stage before irreversible severe respiratory complications take hold and to decrease duration of carriage and avoid the spread of the disease. Furthermore, the cost of treatment is negligible.